Comparison of corneal biomechanics in Sjögren's syndrome and non-Sjögren's syndrome dry eyes by Scheimpflug based device - Long, Qin (Int J Ophthalmol, 2017)
AIM: To compare the corneal biomechanics of Sjögren's syndrome (SS) and non-SS dry eyes with Corneal Visualization Scheimpflug Technology (CorVis ST). METHODS: Corneal biomechanics and tear film parameters, namely the Schirmer I test value, tear film break-up time (TBUT) and corneal staining score (CSS) were detected in 34 eyes of 34 dry eye patients with SS (SSDE group) and 34 dry eye subjects without SS (NSSDE group) using CorVis ST. The differences of the above parameters between the two groups were examined, and the relationship between corneal biomechanics and tear film parameters were observed. RESULTS: The differences in age, sex, intraocular pressure (IOP) and central corneal thickness (CCT) were not significant between the two groups (P>0.05). The tear film parameters had significant differences between the SSDE group and NSSDE group (all P<0.05). Patients in the SSDE group had significantly lower A1-time and HC-time, but higher DA (P=0.01, 0.02, and 0.02, respectively) compared with the NSSDE group. In the SSDE group, DA was negatively correlated with TBUT (rho=-0.38, P=0.03); HC-time was negatively correlated with CSS (rho=-0.43, P=0.02). In the NSSDE group, HC-time was again negatively correlated with CSS (rho=-0.39, P=0.02). CONCLUSION: There are differences in corneal biomechanical properties between SSDE and NSSDE. The cornea of SSDE tends to show less “stiffness”, as seen by a significantly shorter A1-time and HC-time, but larger DA, compared with the cornea of NSSDE. Biomechanical parameters can be influenced by different tear film parameters in both groups.